2015
DOI: 10.5812/jjm.8(5)2015.17296
|View full text |Cite
|
Sign up to set email alerts
|

Use of Restriction Fragment Length Polymorphism to Rapidly Identify Dermatophyte Species Related to Dermatophytosis

Abstract: Background:Dermatophytes are a group of keratinophilic fungi worldwide, which can infect the skin, hair and nails of humans and animals. This genus includes several species that present different features of dermatophytosis. Although, laboratory diagnosis of dermatophytes is based on direct microscopy, biochemical tests and culture, these manners are expensive, time consuming and need skilled staff. Therefore, molecular methods like PCR-RFLP are the beneficial tools for identification, which are rapid and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…In an investigation that was performed by Mohammadi et al. , T. interdigitale, E. floccosum , and T. rubrum were the most common dermatophytes isolated from tinea unguium. They isolated one T. violaceum strain from nail infection.…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation that was performed by Mohammadi et al. , T. interdigitale, E. floccosum , and T. rubrum were the most common dermatophytes isolated from tinea unguium. They isolated one T. violaceum strain from nail infection.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies performed in Iran, Didehdar [6], Abastabar [7], and Mohammadi [8] reported T. tonsurans, T. interdigitale, and M. canis as the most common frequent dermatophytes in TC, respectively. In a study carried out in a rural region in southern Ethiopia among schoolchildren, T. verrucosum was the most common pathogen of TC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Iran have identified the dermatophyte species involved in dermatophytosis, including TC, based on the molecular methods using restriction fragment length polymorphism [6-8]. The treatment of TC requires the administration of oral antifungal drugs in order to penetrate the hair shaft.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, the utility of the PCR-based techniques focusing on various genetic markers have gained popularity to identify the pathogenic fungi. This increased application is due to the fact that the PCR-based techniques have higher speed, sensitivity, specificity, and reproducibility, compared to the conventional methods [ 18 ]. Several authors have previously described the PCR-based procedures, which used specific primers to amplify the DNA fragment of different genes, such as pH-regulated PHR1 and PHR2 [ 19 ], mitochondrial cytochrome b [ 20 ], pH-regulated KER1 [ 21 ], and HWP1 [ 6 ] for the discrimination of C. albicans, C. dubliniensis, and C. africana .…”
Section: Discussionmentioning
confidence: 99%